A novel method to control carryover contamination in isothermal nucleic acid amplification. Issue 77 (15th September 2017) - Ma, Cuiping; Wang, Fuxin; Wang, Xiudan; Han, Lingzhi; Jing, Hao; Zhang, Heng; Shi, Chao
Abstract : We developed a novel method to control carryover contamination in loop-mediated isothermal amplification (LAMP) by primer engineering to carry recognition sites for a restriction endonuclease, providing a robust ability to eliminate carryover contaminants. Abstract : We developed a novel method to control carryover contamination in loop-mediated isothermal amplification (LAMP) by primer engineering to carry recognition sites for a restriction endonuclease, providing a robust ability to eliminate carryover contaminants.